Combining ability and gene action studies in physiological, phenological and yield traits in rice (Oryza sativa L.) - Singh, Ramanjeet; Pandey, Deo Prakash; Kumari, Anjali (Journal of Cereal Research, 2019)
Thirty F1 hybrids from crossing 10 lines and three testers along with their parents were evaluated in RBD with three replications at RWRC, Malan for combining ability and gene action involved in the expression of the traits in rice. Analysis of variance for line × tester mating design with respect to parents, crosses and parents vs. crosses for yield and physiological traits revealed significant differences for almost all the traits studied except total tillers per plant, effective tillers per plant and spikelet fertility in case of parents. Magnitude of σ2D was found to be higher than that of σ2A for all the parameters. The average degree of dominance was observed more than one for all the traits. Narrow-sense heritability was obtained low (<50%) in all the traits studied. Genetic advance was highest for spikelets/panicle (2.36) followed by grains/panicle (1.99), plant height (1.78), gel consistency (0.86) and 1000-grain weight (0.49). Among lines, HPR 2754, HPR 2878 and HPR 2754 were good general combiners for grain yield and contributing traits. The best combinations for sca effects were HPR 2880 × HPR 2143, HPR 2756 × HPR 2720, HPR 2872 × HPR 2720, HPR 2880 × HPR 2612 and HPR 2880 × HPR 2720. The cross HPR 2872 × HPR 2720 showed highest heterosis over standard check for grain yield/plant and its contributing traits. Genotypes/cross combinations viz., HPR 2756 × HPR 2612 and HPR 2769 × HPR 2612 were found have strong aroma. DOI: https://doi.org/10.25174/2249-4065/2019/94698